2011
DOI: 10.4269/ajtmh.2011.11-0057
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Susceptibility to Commonly Used Antimicrobial Agents in Bacterial Pathogens Isolated from Urinary Tract Infections in Rwanda: Need for New Antimicrobial Guidelines

Abstract: Abstract. The aim of this study was to obtain data on susceptibility patterns of pathogens responsible for both community and hospital urinary tract infections (UTIs); and analyzed risk factors for infection caused by ciprofloxacin-resistant Escherichia coli and extended-spectrum β-lactamace (ESBL)-producing strains in Rwanda. Of 1,012 urine cultures prospectively studied, a total of 196 (19.3%) yielded significant growth of a single organism. The most common isolate (60.7%) was Escherichia coli . The antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
63
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 37 publications
12
63
6
1
Order By: Relevance
“…[10][11][12][13][14] Subsequent reports by Muvunyi and others in 2011, showed higher rates of AMR than previously reported among uropathogenic Escherichia coli isolates, suggesting increasing trends for AMR. 15 Quite alarming in that study was the observed high rate of resistance of E. coli to commonly used oral antibiotics to treat urinary tract infections, including amoxicillin (89.3%), ciprofloxacin (41.3%), nitrofurantoin (44.9%), and cotrimoxazole (82.7%). 15 More recently, a study conducted by Ntirenganya and others in 2015, showed that 31.4% and 58.7% of E. coli and Klebsiella isolates, respectively, were resistant to at least one of the third-generation cephalosporins and 8% of E. coli isolates were resistant to imipenem, suggesting extended-spectrum beta-lactamase (ESBL) and carbapenemase-producing strains were present.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[10][11][12][13][14] Subsequent reports by Muvunyi and others in 2011, showed higher rates of AMR than previously reported among uropathogenic Escherichia coli isolates, suggesting increasing trends for AMR. 15 Quite alarming in that study was the observed high rate of resistance of E. coli to commonly used oral antibiotics to treat urinary tract infections, including amoxicillin (89.3%), ciprofloxacin (41.3%), nitrofurantoin (44.9%), and cotrimoxazole (82.7%). 15 More recently, a study conducted by Ntirenganya and others in 2015, showed that 31.4% and 58.7% of E. coli and Klebsiella isolates, respectively, were resistant to at least one of the third-generation cephalosporins and 8% of E. coli isolates were resistant to imipenem, suggesting extended-spectrum beta-lactamase (ESBL) and carbapenemase-producing strains were present.…”
Section: Introductionmentioning
confidence: 98%
“…15 Quite alarming in that study was the observed high rate of resistance of E. coli to commonly used oral antibiotics to treat urinary tract infections, including amoxicillin (89.3%), ciprofloxacin (41.3%), nitrofurantoin (44.9%), and cotrimoxazole (82.7%). 15 More recently, a study conducted by Ntirenganya and others in 2015, showed that 31.4% and 58.7% of E. coli and Klebsiella isolates, respectively, were resistant to at least one of the third-generation cephalosporins and 8% of E. coli isolates were resistant to imipenem, suggesting extended-spectrum beta-lactamase (ESBL) and carbapenemase-producing strains were present. Furthermore, 82% and 6% of Staphylococcus aureus strains were noted to be oxacillin and vancomycin resistant, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies during 1999-2012 in many countries such as Russia, 3 Greece, 4 Sweden, 5 and Rwanda 6 found that E. coli was the most common pathogen causing UTIs, and 97.0%, 93.0%, 85.3%, 62.1%, respectively, of the isolated pathogens in these studies were susceptible to nitrofurantoin. In Greece 4 and Rwanda, 6 99.0% and 92.3%, respectively, of the isolated pathogens were susceptible to fosfomycin.…”
Section: Introductionmentioning
confidence: 75%
“…[3,[6][7][8][9][10][11][12][13][16][17][18]In addition, this is the first study to compare clinical outcomes of fosfomycin in the hospital setting for MDR UTIs and associated antibiotic costs. Neuner et al conducted a retrospective chart review of 41 patients treated with fosfomcycin who had a MDR UTI from 2006 to 2010 but did not compare outcomes to other antibiotics traditionally prescribed for these pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…[19] 57% of patients in their study were administered 3 doses of fosfomycin, whereas only 11.6% of our patients received 3 doses. [18] Their study defined recurrence as having a UTI with the same organism within 3 months of the initial diagnosis, whereas we defined clinical failure as infection with the same organism within 30 days of the original culture. [18] Reid et al reported 54% of patients had recurrence of their UTI.…”
Section: Discussionmentioning
confidence: 99%